Recurrence risk of preterm birth in a subsequent singleton pregnancy after a spontaneous preterm triplet delivery. (March 2020) - Rottenstreich, Amihai; Rottenstreich, Misgav; Ehrlich, Zvi; Ezra, Yosef; Mankuta, David; Yagel, Simcha; Kabiri, Doron; Elchalal, Uriel; Levin, Gabriel
Abstract: Objective: History of prior preterm birth (PTB) represents one of the strongest risk factors for recurrent PTB. Nevertheless, whether the occurrence of PTB in multifetal gestation is associated with increased risk of PTB in subsequent pregnancies remains unclear. We aimed to determine the recurrence risk of PTB in a subsequent singleton pregnancy after a previous spontaneous preterm triplet delivery. Study design: A retrospective matched case-control study. The study group comprised all women with spontaneous preterm trichorionic triplet delivery who had a subsequent singleton pregnancy during 2006–2017 at two university hospitals. A control group of women with spontaneous preterm dichorionic twin delivery and a subsequent singleton pregnancy, was established by matching, four-to-one, according to maternal age, parity, gestational age at delivery, and delivery year. Results: Data from 170 women were analyzed, 34 with preterm triplet delivery and 136 matched control women with preterm twin delivery. Gestational age at the subsequent singleton delivery was higher in those with preterm triplet delivery than in those with preterm twin delivery (median 39 vs 38 weeks, P = 0.02). Women with prior triplet PTB had a significantly lower rate of recurrent PTB as compared with women with prior twin PTB (5.9 % vs. 25.0 %; OR [95 % CI]: 0.19 (0.04, 0.82), P = 0.02) with lower proportions of low-birth weight infants (<2500 g) (0 % vs. 11.8 %, P = 0.04). Conclusions: The risk of recurrent PTB following spontaneous PTB in triplet pregnancy was low compared to preterm twin delivery. These data provide reassurance for those who experienced preterm triplet delivery and suggest the need for further studies to understand the mechanisms contributing to PTB in multifetal pregnancies.